Translation, Quotation, Iterability - Rendall, Steven (TTR)

(untitled) (Association canadienne de traductologie, 1997)
AbstractTranslation, Quotation, Iterability (Walter Benjamin) — Translatability can be considered a special case of the general property of language Derrida called "iterability." By focusing on this property I seek both to clarify the place of translation in Benjamin's thought with respect to other modes of iteration, such as critical commentary and quotation, and to suggest a different way of thinking about translation.Like quotation, translation does not "use" the original text, but rather "mentions" or "names" it. Thus we can understand Benjamin's defense of word-for-word translation (Wörtlichkeit); if translation, like quotation, denotes the text of the original, then what it translates is not the sense of the original, but its word. Similarly, what translation connotes is translation itself considered as a possible act, or to put the point in Benjamin's and Rodolphe Gasché's terms, it communicates translatability.Iterability, translatability, and quotability are that part of the structure of a linguistic entity that differs from the entity itself, and points toward something beyond it. For Benjamin, that beyond is pure language.